Mad honey poisoning in man and rat - YEGEN, BERRAK (My University, 1991)
Grayanotoxins are known to occur in the honey produced from the nectar of Rhododendron ponticum growing on the mountains of the eastern Black Sea region of Turkey and also in Japan, Nepal, Brazil, and some parts of North America and Europe. Two cases of honey intoxication are presented here. Both of the patients experienced severe bradycardia and hypotension after ingestion of honey which was brought from Trabzon, Turkey. Microscopical examination showed Rhododendron ponticum pollen tetrades. Anesthetized albino rats were injected intraperitoneally with toxic honey extract doses equivalent to 1 or 5 g honey/kg. Dose-dependent hypotension, bradycardia and respiratory rate depression were observed. When marked bradycardia (approximately 75% of control value) was reached, rats were given atropine sulfate (2 mg/kg, i.p.) or AF-DX 116 (20 mg/kg, i.p.). Atropine sulfate improved both bradycardia and respiratory rate depression. AF-DX 116, which is a selective M2-muscarinic receptor antagonist, restored only heart rate, but not the respiratory rate depression. These results suggest that M2-muscarinic receptors are involved in cardiotoxicity of grayanotoxin.
Keywords: Female; Humans; Middle Aged; Animals; Aged; Turkey; Male; Rats; Honey; Respiration; Pirenzepine; Diterpenes; Bradycardia; Parasympatholytics; Atropine; Hypotension